Temporal changes of key marine habitats in the World Biosphere Reserve of Cu Lao Cham - Hoi An, Quang Nam province - Nguyen Van , Long; Tong Phuoc , Hoang Son (Vietnam Journal of Marine Science and Technology, 2021)
Assessments of marine habitats have played an essential role in the management and sustainable uses of marine biodiversity resources. Spatial and temporal changes in distribution and area of crucial marine habitats in the World Biosphere Reserve of Cu Lao Cham - Hoi An were assessed using remote sensing technology (Landsat 5-TM, SPOT4, and AVNIR2 Sentinel 2-MS) and aerial images in combination with ground-truthing at 60 key sites in the year of 2016 and back-interpretation for the years of 2004 and 2008. This study shows some 579 ha of coral reefs, 117 ha of mangrove forest (mainly by Nypa palm), and 43 ha of seagrass beds recorded in 2016. There was some 112.5 ha, including 77.1 ha of the Nypa palm in the Thu Bon estuaries, 34.6 ha of seagrass beds (Bai Ong and Bai Huong in Cu Lao Cham islands), and 0.8 ha of coral reefs lost between 2004 and 2016 due to development of infrastructure and marine culture. The declines of the Nypa palm and the seagrass beds in the Thu Bon estuaries have been threatening to the maintenance of essential nursery grounds of target species, especially in the area surrounding the Nypa palm forest “rung dua bay mau” at Cam Thanh commune.